Data sharing management model in networked collaborative environment / Nasiroh Omar, Siti Zaleha Zainal Abidin and Suzana Ahmad - Omar, Nasiroh; Zainal Abidin, Siti Zaleha; Ahmad, Suzana (Research Management Institute (RMI), 2012)
Networked collaborative environment is a computer mediated system for interaction between users (Abidin et a/., 2006). Dickerson (2008) defines networked collaborative system as Virtual reality spaces that enable participants to collaborate and share objects as if physically presence at the same place'. Communication in the networks involves many processes (either clients or servers) that need to be coordinated. The coordination is usually depended on the application. In recent years, most applications in networked collaborative systems not only facilitate communication but also improve collaborative works (Masud and Kiringa, 2007; Abidin et a/., 2004). Most collaborative activities involve data sharing and movements between parties. Data is valuable to relevant parties. For example, employee, supplier and stock data are all valuable to the related companies (Abidin et a/.., 2010; Hristidis et a/., 2009). Research data is also a valuable resource that usually requires much time and money to be produced. According to Wainhouse Research (2002) and Cheung (2006), data sharing leads to facilitating new collaborations between data users and data creators; reducing cost of duplicated data collection and encouraging the improvement and validation of data collection. Though data sharing leads to good things, it also raises common problems in management issues. Server-centric data management methodology occurs in distributed heterogeneous collaborative design such as openness, scalability and flexibility (Atzeni et al., 2002). In the server-centric data management mode, data is usually stored in the server side. For the authorization, a user can login into server systems for data management and performs data update operation (Rosen and Rimor, 2009). The server records the updated data according to the operation logs. Then, it transmits the updated information over the network. In the whole process, all activities are fulfilled by the server. Thus, server is heavily burdened that leads to the degrading reliability of network management. For example, when collaborative activities involve several groups of partner enterprises, issues of security in sensitive design for the server system must be seriously managed (Ferrin et al., 2005; Eaglestone and Ridley, 2001; Ruan and Vardharajan, 2010).